2015
DOI: 10.1007/s11745-015-4001-4
|View full text |Cite
|
Sign up to set email alerts
|

Cistus ladanifer L. Shrub is Rich in Saturated and Branched Chain Fatty Acids and their Concentration Increases in the Mediterranean Dry Season

Abstract: The Cistus ladanifer L. shrub is a widespread species of the Mediterranean region that is available as a feed source for ruminants all the year round, constituting a source of energy and nutrients when most of the vegetation is dry. However, there is no trustworthy information about the fatty acid composition of C. ladanifer, as well as no information about the seasonal and age related changes in their fatty acid composition. Thus, we collected the aerial parts of C. ladanifer plants of two age groups [young v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…(). However, recent results have shown that the total fatty acid content of the aerial part of C. ladanifer varies from 5·0 to 9·0 m g kg −1 DM, only about 10% of the EE (Guerreiro et al ., ). In the present study, the aerial parts of C. ladanifer comprised a mixture of leaves, soft stems and reproductive organs.…”
Section: Discussionmentioning
confidence: 97%
“…(). However, recent results have shown that the total fatty acid content of the aerial part of C. ladanifer varies from 5·0 to 9·0 m g kg −1 DM, only about 10% of the EE (Guerreiro et al ., ). In the present study, the aerial parts of C. ladanifer comprised a mixture of leaves, soft stems and reproductive organs.…”
Section: Discussionmentioning
confidence: 97%
“…The genus Cistus is characterized by having species with a high content of secondary metabolites [17]. Specifically, the leaves of these three species have a high content of phenolic compounds [18][19][20][21]. Erica australis and Arbutus unedo are also characterized for their high content of phenolic compounds and, particularly, condensed tannins [22,23].…”
Section: Selection Of the Studied Plantsmentioning
confidence: 99%
“…Therefore, one note of caution must be made on the interpretation of the effects of dietary Cistus on deposition of biohydrogenation intermediates in meat, as the effects of dietary Cistus and C18 unsaturated FA intake might be confounded due to changes in diet ingredients and to differences of voluntary feed intake. This is clearly perceived from the interaction between both main factors (Cistus and oil) on FA intake data, particularly if we take in consideration that Cistus has a low content in PUFA (Guerreiro et al, 2015). For this reason, whenever a significant effect of Cistus inclusion level was observed, it was confirmed by complementary regression analysis using the intake of condensed tannins and C18 unsaturated FA as independent variables.…”
Section: Discussionmentioning
confidence: 70%